Communication strategies of corporate social responsibility program on sexual reproductive health “Eduka5eks” - Arindita, Ruvira; Naura, Firdha (Faculty of Communication Sciences Universitas Padjadjaran, 2023)
The Indonesian government has long focused on sexual reproductive health issues among the younger generation. Contraceptive brand, Durex-Reckitt Benckiser, created a reproductive education program for young people and parents called Eduka5eks. This study aims to find out how the Corporate Social Responsibility (CSR) communication strategy is in the Eduka5eks reproductive health education program. The research method uses descriptive qualitative. Data were obtained through interviews with brand managers, event project managers, and online observations. The results showed that the communication strategy of the Eduka5eks program consisted of research, planning, implementation, evaluation and reporting. The Eduka5eks program emphasizes research and planning to determine the program’s key messages contained in the logo. Furthermore, the CSR communication strategy in the Eduka5eks program focuses on “interacting” strategies that involve various stakeholders to communicate the program and use controlled media, such as websites, social media brands, and press releases. Another strategy, namely “informing” is carried out as seen in CSR communication media that connects CSR with the core business objectives of the brand. Media that is not controlled in news in online media is in the form of coverage of events carried out by brands. In the aspect of communication development strategy, the strategy implemented is a media and participatory strategy because this program focuses more on the use of various media and nominating brand ambassadors. Suggestions for brands are the need to increase the role of peer educators and expand the program to youth in rural areas.